EDITORIAL SCOPE – STRUCTURE AND MATERIAL EDITION - Kueh, Ahmad Beng Hong (Journal of Civil Engineering, Science and Technology, 2022)
This first-ever Editorial Scope of the Journal of Civil Engineering, Science and Technology (JCEST) touches the scientometrics of one of the main civil engineering disciplines, structure and material, in the publication realm. This brief editorial piece highlights the emerging and highly investigated themes in the last 5 years by gathering information from the wealth of the freely accessible Scopus database. Also, the most researched and published areas of JCEST within this period from the perspective of popular keywords are assembled and presented. The overlapped terms of the widely researched topics from the two sources are then captured to show their common publication territories of attention. This exercise aims to offer a brief guide for authors to better plan and navigate their knowledge quest to fit the currently trailblazing research curiosity and interest.